The Effectiveness Of The Massed And Distributed Methods On The Low Pass Skill In Volleyball Game - Saleh, Muhammad Syahrul; Syahruddin, Syahruddin; Saleh, M. Sahib (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2023)
The aims this reseach to determine the effect of method of massed on the volleyball skills of passing, the effect of distributed of method on the volleyball skills of passing, and to know the difference between the methods of massed and distributed method for passing the volleyball skills. This type of research is a thrue experiment with Randomized Group Pretest - Posttest Design. The independent variable is the method of massed and distributed methods while the dependent variable was passing the volleyball skills. The subjects were male students grade 2 SMA Negeri 1 Gangking district Gantarang Bulukumba learning year 2011/2012, as many as 30 people are purposive random sampling. The results showed that there was a significant effect of massed method for passing down skills in the game of volleyball (p <0.05), there was a significant effect of distributed method for passing down skills in the game of volleyball (p <0.05), and better distributed method increases passing down the skills in the game of volleyball than massed method (p <0.05).